2017
DOI: 10.1155/2017/5402748
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Toxic Activity of Fermentation Extracts fromBacillus thuringiensisvar.israelensisafter More Than Three Decades of Storage

Abstract: This study was carried out to determine the persistence of toxicity of fermentation extracts of Bacillus thuringiensis var. israelensis after more than three decades of storage. For this purpose, a population of Aedes aegypti was established. The mortality rate of 20 spore-crystal extracts purified using the acetone-lactose coprecipitation method was measured and evaluated by bioassays according to a modified WHO protocol. The extracts with the highest mortality rate were determined in triplicate by their LD50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…On the other hand, a low level of larval mortalities was observed in all the treatments as the concentrations of Vectobac 12AS decreases. This finding is in agreement with the findings of previous research [28] who also reported that most of these Bacillus thuringiensis israelensis extracts showed some toxic activity toward mosquito larvae in high concentrations, but their activity decreased as the dilution increased. This could be attributed to the fact that, much higher concentrations of Bti formulation are required in order to induce mortality in Anopheline larvae than in any other larval mosquito specie.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, a low level of larval mortalities was observed in all the treatments as the concentrations of Vectobac 12AS decreases. This finding is in agreement with the findings of previous research [28] who also reported that most of these Bacillus thuringiensis israelensis extracts showed some toxic activity toward mosquito larvae in high concentrations, but their activity decreased as the dilution increased. This could be attributed to the fact that, much higher concentrations of Bti formulation are required in order to induce mortality in Anopheline larvae than in any other larval mosquito specie.…”
Section: Discussionsupporting
confidence: 93%
“…Twenty samples of the strain HD-500 and HD-567 of Bti fermentation extracts from the collection of Dulmage et al [44] recovered by lactose-acetone coprecipitation during the period from 1978 to 1983 maintained their residual toxic activity against the mosquito Aedes aegypti. All extracts evaluated presented toxicity at the highest tested doses (1000 ppm), and two of the stored extracts (3260 and 3501) showed LD50 of 0.12 and 1.16 ppm, respectively [40].…”
Section: Bti Strain Collectionmentioning
confidence: 92%
“…Dulmage sets up the basis for the fermentation and formulation procedures of Bt culture extracts for their commercialization [39] and were among the most important pioneers in the development of technologies for the implementation of Bt as a biological pest control agent. He established diverse methodologies for mass production product formulation and power standardization [40].…”
Section: Howard T Dulmage's Methods and Contributions On Btmentioning
confidence: 99%
“…Five Bti fermentation extracts with the code: 3260, 3501, 3691, 3696, and 3756, respectively, were produced by coprecipitation lactose-acetone method by Dulmage et al (1970) at the US Department of Agriculture, Agricultural Research Service (USDA-ARS) from the strains HD-500 and HD-567, chosen from the previous work of Galán et al (2017). During the storage period, all extracts were stored in dark and dry conditions exclusively for this purpose at 25 ± 3°C in sterile and hermetic bottles.…”
Section: Bacillus Thuringiensis Var Israelensis Strainsmentioning
confidence: 99%
“…A recent study was undertaken to evaluate the persistence of 20 Bti extracts stored for prolonged periods of time. All extracts presented biological activity at high concentrations against A. aegypti larvae, demonstrating the biological persistence of crystal proteins (Galán et al 2017). The reconstitution and characterization of Bti toxins has never been evaluated after long storage periods, nor observed whether they have retained their genetic capacity and maintained the same biologic activity after reactivation.…”
Section: Introductionmentioning
confidence: 99%